Using the Implicit Relational Assessment Procedure (IRAP) to assess the verbal relations entailed on experiential avoidance: A pilot study (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Experiential Avoidance (EA) is an attempt to avoid contact with aversive private events or correlated stimuli that might evoke or elicit them. The present research investigated the correlation between an explicit measure of EA, the AAQ-II, and an implicit measure, based on the Implicit Relational Assessment Procedure (IRAP). After responding to the AAQ-II, participants were submitted to a IRAP task that assessed the response latency (true or false) to phases indicating acceptance or avoidance of positive or negative private events. There were four IRAP trial types: accept +, accept -, avoid + and avoid -. Responses were faster to the following relations: “accept +, true” and “avoid -, true”. The comparison between groups with different latency criteria (2.500 ms vs. 2.000 ms) suggested that the group with a stricter criterion (2.000 ms) had stronger IRAP effect and showed a correlation between the IRAP trial type “avoid -” and the AAQ-II scores.
Keywords: experiential avoidance; AAQ-II; IRAP; implicit measures; adults